1991
DOI: 10.1093/ageing/20.5.379
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Inhaled Bronchodilator Delivery Systems for Elderly Patients

Abstract: A prospective study of inhaler technique using aerosol metered dose inhalers (MDIs), Rotahalers and a breath-activated device (Aerolin Autohaler) was undertaken to assess how effectively elderly patients use their inhalers. Fifty-one patients aged 67-89 years (mean 77.4 years) were enrolled. Peak flow, FEV1 and FVC were recorded, before and after inhalation of 2.5 mg of salbutamol via a nebulizer, to assess the extent of reversible airways obstruction. Inhaler technique was assessed using a scoring system, bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 0 publications
4
16
0
Order By: Relevance
“…Patients who were first prescribed an MDI in a hospital were significantly more likely to be competent than were those who were prescribed an MDI by a general practitioner. Elderly patients requiring MDI therapy should be carefully selected and properly instructed by the prescribing doctor (56)(57). The use of large volume spacers (LVS) improves the inhalation technique in elderly patients, and most of them prefer this device to the MDI alone.…”
Section: How Different Should Asthma Treatment Be In the Elderly?mentioning
confidence: 99%
“…Patients who were first prescribed an MDI in a hospital were significantly more likely to be competent than were those who were prescribed an MDI by a general practitioner. Elderly patients requiring MDI therapy should be carefully selected and properly instructed by the prescribing doctor (56)(57). The use of large volume spacers (LVS) improves the inhalation technique in elderly patients, and most of them prefer this device to the MDI alone.…”
Section: How Different Should Asthma Treatment Be In the Elderly?mentioning
confidence: 99%
“…Our study was supported by some other studies where the type of inhaler was a determinant of poor use. 30,31 Repetition of training at regular intervals enhances the technique of correct inhalation. This fact is also supported by studies as a study by Kamps et al which demonstrated that in newly referred children with asthma correct inhalation technique with MDI and spacer improved from 78.6 to 100% after three instruction sessions.…”
Section: Discussionmentioning
confidence: 99%
“…Interest in this field was stimulated by a study carried out by the author in 1986 which showed that 40 percent of community dwelling patients with a mean age of 80 years had a completely inadequate technique with a metered dose inhaler [20]. A number of subsequent surveys demonstrated a similar finding, and the use of less technically demanding devices has been shown to reduce this percentage only moderately, unless a substantial programme of screening and training was undertaken [23][24][25][26][27]. In most studies, the commonest errors in technique have been related to poor coordination between actuation of devices and inhalation; sometimes referred to as hand-lung in-coordination [20,28,29].…”
Section: Typical Errors In Inhaler Techniquementioning
confidence: 99%
“…The most important factors in this domain centre around manual dexterity, and to a lesser extent, vision [8,10,19,25,28]. There is ample evidence that patients with weak or painful hands are unable to use inhalers that require actuation by compression of a valve, such as a pressurized metered dose inhaler [19].…”
Section: Physical Barriers To An Adequate Inhaler Techniquementioning
confidence: 99%